Unresolved Questions Concerning Mammalian Sperm Acrosomal Exocytosis - Buffone, Mariano G. (Society for the Study of Reproduction, Inc., 2014)
In recent years, the study of mammalian acrosomal exocytosis has produced some major advances that challenge the long-held, general paradigms in the field. Principally, the idea that sperm must be acrosome-intact to bind to the zona pellucida of unfertilized eggs, based largely on in vitro fertilization studies of mouse oocytes denuded of the cumulus oophorus, has been overturned by experiments using state-of-the-art imaging of cumulus-intact oocytes and fertilization experiments where eggs were reinseminated by acrosome-reacted sperm recovered from the perivitelline space of zygotes. In light of these results, this minireview highlights a number of unresolved questions and emphasizes the fact that there is still much work to be done in this exciting field. Future experiments using recently advanced technologies should lead to a more complete and accurate understanding of the molecular mechanisms governing the fertilization process in mammals.